MODERN DIRECTION FOR IMPROVING THE QUALITY OF TRAINING STUDENTS OF DENTAL FACULTY - M.V. Storozheva; S.N. Grigorov; L.P. Rekova (Український стоматологічний альманах, 2018)
In various studies of the structure of human activities, including professional ones, the main thing in this context is given to its components, as the motive and purpose. These components affect the personal and professional development of medical students and medical interns. Readiness for continuous improvement of professional knowledge and skills positively affects the attitude to the chosen specialty. The search for methods of motivation for the retention and use of knowledge, practical skills in students is an important task in teaching one of the most interesting and at the same time the most difficult dental disciplines as “Dental Surgery”.